2017
DOI: 10.21608/eajb.2017.12180
|View full text |Cite
|
Sign up to set email alerts
|

The Egyptian Thripid Species in Olive Groves at Ismaialia, Egypt

Abstract: Thripid species were represented by seven species in olive groves at Ismailia governorate during 2013 and 2014 on different cultivars (El-Egazy; Manzanillo and Pequal) and weeds in olive groves. The species are Frankliniella occidentalis (Pergaade); Thrips microchatus Karny; Scirtothrips aurantii Faure; Haplothrips cahirensis Karny; Dendrothrips eremicola Priesener; Thrips tabaci Lindeman and Sericothrips kassimanus Priesener. First three species are represented in olive trees as a new host. The second three w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…and Pseudodendrothrips mori were placed in the same clade. This result agree with the morphological studies carried out by other authors (Mound, 1999;Alavi, 2014;Balou and Dosty, 2015 ;Mound andTree, 2016 andAgamy et al, 2017) which reported that both genus Dendrothrips and Pseudodendrothrips were classified under the same subfamily Dendrothripinae. While, Aptinothrips rufus was placed under the other subfamily (Thripinae).…”
Section: Dendrothrips Eremicola Priesenersupporting
confidence: 93%
See 4 more Smart Citations
“…and Pseudodendrothrips mori were placed in the same clade. This result agree with the morphological studies carried out by other authors (Mound, 1999;Alavi, 2014;Balou and Dosty, 2015 ;Mound andTree, 2016 andAgamy et al, 2017) which reported that both genus Dendrothrips and Pseudodendrothrips were classified under the same subfamily Dendrothripinae. While, Aptinothrips rufus was placed under the other subfamily (Thripinae).…”
Section: Dendrothrips Eremicola Priesenersupporting
confidence: 93%
“…The images and classification of species are given in Figures (1-4). The studied species were previously identified by morphological characters (Agamy et al, 2017). The data analysis showed that nucleotide sequence of 18s rDNA of the three tested samples were similar in size 700 bases ( Figure 5).…”
Section: Identification Of Studied Speciesmentioning
confidence: 77%
See 3 more Smart Citations